2019
DOI: 10.1017/jfm.2019.397
|View full text |Cite
|
Sign up to set email alerts
|

The secondary instabilities of stationary cross-flow vortices in a Mach 6 swept wing flow

Abstract: The secondary instabilities of stationary cross-flow vortices in a Mach 6 swept wing flow are studied using Floquet theory. High-frequency secondary instability modes of ‘y’ mode on top of stationary cross-flow vortices, and ‘z’ mode concentrating on the shoulder of the stationary cross-flow vortex are found. The most unstable secondary instability mode is always the ‘z’ mode as in incompressible swept wing flows. A new secondary instability mode concentrating on the trough of the stationary cross-flow vortex … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 34 publications
(16 citation statements)
references
References 36 publications
4
12
0
Order By: Relevance
“…[15], the large frequency bandwidth of this mode appears consistent as it lies in the relatively thin, inclined shear layer associated with the overturning contours of axial velocity from the strong crossflow vortex. Its shape and location are similar to the 'z' mode obtained in previous stability studies in swept-wing three-dimensional boundary layers [32]. The phase speed of each mode is shown in Fig.…”
Section: B Linear Instabilities Of the Roughness Wakesupporting
confidence: 76%
“…[15], the large frequency bandwidth of this mode appears consistent as it lies in the relatively thin, inclined shear layer associated with the overturning contours of axial velocity from the strong crossflow vortex. Its shape and location are similar to the 'z' mode obtained in previous stability studies in swept-wing three-dimensional boundary layers [32]. The phase speed of each mode is shown in Fig.…”
Section: B Linear Instabilities Of the Roughness Wakesupporting
confidence: 76%
“…The swept wing is modelled by a swept parabolic body, which was widely adopted in previous investigations concerning cross-flow instability (see Mack & Schmid 2010; Xu et al. 2019; Xi et al. 2021).…”
Section: Problem Description and Governing Equationsmentioning
confidence: 99%
“…Recently, combined NPSE, SIT and DNS investigations were performed by Xu et al. (2019) and Chen et al. (2021 a ) for the flow over a Mach-6 swept parabola.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3]), especially in hypersonic conditions. Therefore, in the last decades, considerable efforts have been made towards building a fundamental understanding to the transition of hypersonic three-dimensional boundary layers by wind tunnel experiments [4][5][6][7][8][9], theoretical analyses [10][11][12][13], direct numerical simulations (Chen et al: Transition of hypersonic boundary layer over a yawed blunt cone, submitted) (Chen et al: Stationary cross-flow breakdown in a high-speed swept-wing boundary layer, submitted) and flight tests (see overview [14]). Nevertheless, much is still unknown.…”
Section: Introductionmentioning
confidence: 99%
“…A typical example is the breakdown of crossflow vortices. In both the low-and high-speed flows with crossflow, it has been found that the z-type (produced by the spanwise or azimuthal gradients of the streamwise mean flow) secondary crossflow instability is responsible for the natural transition process [17] (Chen et al: Stationary cross-flow breakdown in a high-speed swept-wing boundary layer, submitted), although stability analyses [13,17] also detected the y-type (produced by the wall-normal gradient of the streamwise mean flow) secondary crossflow instabilities.…”
Section: Introductionmentioning
confidence: 99%